2017
DOI: 10.1139/apnm-2016-0572
|View full text |Cite
|
Sign up to set email alerts
|

Food parenting practices and their association with child nutrition risk status: comparing mothers and fathers

Abstract: In Canada, little is known about how food parenting practices are associated with young children's dietary intakes and no studies have examined food parenting practices of Canadian fathers. This study aimed to examine associations between food parenting practices and preschool-age children's nutrition risk. We conducted a cross-sectional analysis of thirty-one 2-parent families; 31 mothers, 31 fathers, and 40 preschool-age children. Parents completed an adapted version of the Comprehensive Feeding Practices Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 26 publications
1
44
1
7
Order By: Relevance
“…A similar number of studies, however, reported no differences in the types and levels of food parenting practices used by mothers and fathers 66‐74 . When looking at the influence of fathers' food parenting on child outcomes, studies reported that fathers' use of controlling food parenting practices is linked with higher consumption of unhealthy foods or higher rates of overweight among children 29,63,75‐78 and their use of responsive food parenting practices, such as modeling healthy eating behaviors, is linked with positive diet and weight outcomes in children 76,78‐80 . Three studies reported no effects of fathers' food parenting on children's outcomes 81‐83 …”
Section: Resultsmentioning
confidence: 99%
“…A similar number of studies, however, reported no differences in the types and levels of food parenting practices used by mothers and fathers 66‐74 . When looking at the influence of fathers' food parenting on child outcomes, studies reported that fathers' use of controlling food parenting practices is linked with higher consumption of unhealthy foods or higher rates of overweight among children 29,63,75‐78 and their use of responsive food parenting practices, such as modeling healthy eating behaviors, is linked with positive diet and weight outcomes in children 76,78‐80 . Three studies reported no effects of fathers' food parenting on children's outcomes 81‐83 …”
Section: Resultsmentioning
confidence: 99%
“…Fathers might have a protective role in the development of child psychopathology, particularly when they actively parent (Sadeh‐Sharvit et al, ). Furthermore, fathers' modelling of healthy eating behaviours has been shown to be associated with lower nutrition risk (Watterworth et al, ). However, this was not assessed in the present paper and should be addressed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Posteriormente ao uso dos filtros ou limites, foram excluídos 1.388 trabalhos e, por meio da leitura dos títulos e resumos, permaneceram 54 artigos elegíveis. Foi realizada a leitura minuciosa e integral de 14 Palfreyman et al, 2014 33 Antoniou et al, 2015 25 Remy et al, 2015 29 Russell et al, 2015 27 Ho mann et al, 2016 22 Anna Ek et al, 2016 25 Holley et al, 2016 31 Bennett et al, 2016 35 Russell et al, 2016 27 Tylka et al, 2016 15 Steinsbekk et al, 2016 16 Blaine et al, 2017 17 Melo et al, 2017 32 Crianças na faixa etária entre 3 a 6 anos de idade, uma amostra N= 439 18 Klazine et al, 2017 19 Haycraft et al, 2017 46 Lindsay et al, 2017 20 Fries et al,…”
Section: Resultsunclassified